Perception of Pain in Children With Covid-19 Using DWT (Drawing, Writing And Tell) at Hospital For Emergency Covid-19 Management Athlet College Kemayoran - Nyimas Heny Purwati; Rahayu Maharani (Universitas STRADA Indonesia, 2021)
One of the most common symptoms that children with COVID-19 experience was pain. Pain perception in children was influenced by the level of understanding and how to communicate. Draw, write and tell Method (DWT) was a method used to assess pain in children. This study used a qualitative method with a descriptive phenomenology approach. The study participants consisted of six children aged 4-10 years who were treated with COVID-19 who could draw or like to draw and were able to write and tell the results they drew. Data analysis used the analysis stage according to Colaizzi. The findings of this study included (1) The physical changes felt by children before being confirmed by COVID-19. (2) The discomfort felt by the child when the swab is examined. (3) Child psychological impact. (4) Child Social Impact